Novel insights into Notch signaling in tumor immunity: potential targets for cancer immunotherapy - Wang, Man; Yu, Fei; Zhang, Yuan; Li, Peifeng (Frontiers in Immunology, 2024)
Notch signaling pathway is a highly conserved system of cell-to-cell communication that participates in various biological processes, such as stem cell maintenance, cell fate decision, cell proliferation and death during homeostasis and development. Dysregulation of Notch signaling has been associated with many aspects of cancer biology, such as maintenance of cancer stem-like cells (CSCs), cancer cell metabolism, angiogenesis and tumor immunity. Particularly, Notch signaling can regulate antitumor or pro-tumor immune cells within the tumor microenvironment (TME). Currently, Notch signaling has drawn significant attention in the therapeutic development of cancer treatment. In this review, we focus on the role of Notch signaling pathway in remodeling tumor immune microenvironment. We describe the impact of Notch signaling on the efficacy of cancer immunotherapies. Furthermore, we summarize the results of relevant preclinical and clinical trials of Notch-targeted therapeutics and discuss the challenges in their clinical application in cancer therapy. An improved understanding of the involvement of Notch signaling in tumor immunity will open the door to new options in cancer immunotherapy treatment.